(untitled) (Inovasi, 2023)
The research aim to describe pattern of waste management and local government policies in waste management. This research was analyzed qualitatively with a descriptive approach and quantitatively with a simple statistical approach (without statistical tests). The results show that the pattern of waste handling in Labuhanbatu Regency is transporting waste from the source directly to the landfill so that the carrying capacity and capacity of the landfill is overcapacity. Community empowerment in waste management in Labuhanbatu Regency is still very minimal, with the percentage of people who have participated in community empowerment programs and activities carried out by the local government and other agencies per each assessment indicator as follows: environmental health counseling (10.16%); socialization about waste management and similar activities (13.115%); participation of members/organizational administrators who care about waste management (6.885%); waste management training to be something economically valuable (6.885%); getting the opportunity to work in waste recycling management (1.311%); getting waste management facilities (1.311%); getting business capital for waste management (1.311%); getting economic benefits from waste management (2.295%); producing several products from waste recycling management (4.262%); and protection efforts from the local government when there is a conflict over waste management (3.607%). Labuhanbatu Regency already has 2 regulations and laws related to waste management, namely: Peraturan Daerah Kabupaten Labuhanbatu No. 8 Tahun 2017 tentang Pengelolaan Sampah, and Peraturan Bupati Labuhanbatu No. 48 Tahun 2021 tentang Pelimpahan Sebagian Kewenangan Pengelolaan Persampahan kepada Camat di Lingkungan Pemerintah Kabupaten Labuhanbatu. Keywords: waste management, community empowerment, government policy